Оценка методов построения черепных имплантатов - Шамраева, Е. О. (ХНУРЭ, 2008)
This work is devoted the comparative analysis of methods construction of cranial implantâtes in dependence of initial data. The manual and automated methods of construction of cranial implantates are here analysis. The initial data are КТ-images and X-ray images.
Keywords: имплантат; биомединженерия